Erratum and Addendum: “Contractor’s Attitude towards Risk and Risk Management in Construction in Two Western Provinces of Vietnam” - Phan, V. T. (Engineering, Technology & Applied Science Research, 2021)
Since the publication of the original paper in vol. 10, no. 6 of this journal [1], the author has detected several misprints and errors that are correct here, in the order in which they appear in the original paper.